Neue Ansätze und Indikationen zur Plättchenfunktionsdiagnostik in der Kardiologie - Ivandic, B.; Frey, N. (Hämostaseologie, 2011)
Inhibiting platelet function is a key therapeutic principle in cardiology because platelets play a pivotal role in triggering cardiovascular events. In addition to acetylsalicylic acid, a cyclooxygenase inhibitor, ADP-receptor blockers are frequently used for anti-platelet therapy. This therapy does not abolish platelet activation and aggregation. Platelets may still be activated by alternative routes such as the thrombin receptor-mediated pathway. New, more potent inhibitors of platelet function continue to lower the risk of ischaemic events but several trials and clinical registries have also shown that this advantage was frequently offset by an increased risk of bleeding complications. As a consequence, the individual risk of ischaemia and bleeding of a patient must be taken into consideration to select the platelet inhibitor offering the best benefit-risk ratio. Modern laboratory diagnostics may help to achieve this goal by complementing functional platelet tests with pharmacogenomic analyses consistent with the idea of „personalized medicine“.
Keywords: Platelet; coronary artery disease; myocardial infarction; thienopyridin